The Maternal Body as a Space: Examining the Visuality of Marian Pregnancy in Late Medieval Europe - Andal, Aireen Grace (Open theology, 2021)
This work offers a theoretically informed analysis of the characterization of maternity in religion using a spatial lens. The maternal body as a space is used as an analytical framework to discuss how Mary’s pregnancy is located and spatialized in Christianity. Through examining selected medieval Marian iconography, this work discusses what kind of space Mary’s body represents in the Christian doctrine. Analysis shows three central themes on the characterization of the maternal body as a space: (1) as a transitional space, (2) as a landmark, and (3) as a liminal space. The images of Marian pregnancy show that the maternal body is beyond its biological purpose in the Bible, but serves as a space that enables various interactions and spiritual events. The examination of Mary’s maternal body as a space offers an alternative perspective to discuss Mary’s character as a point of interface for Christian doctrines, biblical periods, and the Scriptures. In many ways, understanding Mary’s maternal body as a space speaks about the complexities and unveiled aspects of maternity’s role in religion. This work hopes to spark further discussions on how the maternal body intersects with spatiality in the context of religion.